Awareness Through Movement and Swiss Ball Exercise on Muscle Weakness among Subjects with Postural Syndrome. - R., Gowtham chandar; kumaresan A.; Suganthirababu, Prathap; Srinivasan, Vignesh; Vishnuram, Surya; Priyadharshini K.; Alagesan, Jagatheesan (Indian Journal of Physiotherapy & Occupational Therapy)
Background: A general definition of Postural syndrome is a lack of muscle strength or the quality or quantity of movements. This is typically accompanied by one or more of the following all of the joints in the body have an effect on body posture, which is the alignment of a person's body parts with respect to one another and their surroundings at a specific moment in time. Purpose: To compare the effectiveness of Awareness through movements and swiss ball exercise on postural syndrome patients. Materials and Methods: A total of 28 individuals were chosen based on the inclusion and exclusion criteria from Sai Charan physiotherapy clinic, Arakkonam, Ranipet, Tamil Nadu,India. After explaining the treatment's safety and ease of use to the participants, a signed agreement was acquired. Group A [14N] Awareness through movements are given GroupB[14N] Swiss ball movements are given. The pre test and post test results were obtained through Patient specific functional scale. Study duration : 4 Weeks . The entire process was performed from November 2022 to March 2023. Results: As a result, swiss ball exercise is more effective than awareness through movement by analyzing the statistical values of pre test and post test. Conclusion: The study's goal is to evaluate its effects. of swiss ball movement exercise and awareness through movements postural syndrome individuals in the society.